ETIKA HUMOR DALAM DAKWAH: ANALISIS KONTROVERSI CERAMAH GUS MIFTAH - Ridwan, Muhammad; Arifin, Zaenal (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2024)
The ethics of humor in da'wah is a crucial issue, particularly in delivering Islamic messages inclusively and respectfully. This article analyzes the controversy sparked by Gus Miftah's joke about an iced tea vendor, which drew both support and criticism from the public. The study aims to explore the ethical boundaries of humor in da'wah to prevent misunderstandings or resistance from audiences. Using a descriptive qualitative method, data were collected through content analysis of the viral sermon and public responses to the joke. This article addresses a research gap by examining humor in da'wah as a strategic yet potentially divisive element, which has rarely been studied from the perspective of Islamic ethics. The novelty of this study lies in its critical analysis of humor in da'wah, considering cultural sensitivities and Islamic values. The findings reveal that humor violating ethical principles can lead to misunderstandings, damage a preacher's reputation, and incite division. Thus, ethical guidelines are essential for utilizing humor as an effective and harmonious da'wah strategy.